Scalable routing protocols for mobile ad hoc networks. - Xiaoyan Hong
The growing interest in mobile ad hoc network techniques has resulted in many routing protocol proposals. Scalability issues in ad hoc networks are attracting increasing attention these days. We survey the routing protocols that address scalability. The routing protocols included in the survey fall into three categories: flat routing protocols; hierarchical routing approaches; GPS augmented geographical routing schemes. The article compares the scalability properties and operational features of the protocols and discusses challenges in future routing protocol designs
Keywords: GPS augmented routing schemes; Flat routing protocols; Geographical routing schemes; Hierarchical routing; Mobile ad hoc networks; Operational features; Scalability properties; Scalable routing protocols